The WikiLeaks Paradigm Paradoxes and Revelations - Marmura, Stephen M. E. (Springer International Publishing, 2018)
WikiLeaks poses a unique challenge to state and commercial institutions. This book considers the whistleblower platform's ongoing importance, focusing on the informational and communicative paradoxes it faces, and the shifting strategies it has adopted over time. Attention to these matters provides insight into the nature of the contemporary networked, post-truth media environment, and the types of factors likely to affect the success of activist groups today. Chapter 1 introduces WikiLeaks' significance as a novel expression of counterpower, outlining the disclosures marking its career. Chapters 2 through 4 address the dilemmas confronting WikiLeaks in its attempts to engage the public with and without the cooperation of mainstream news organizations. Chapter 5 appraises how WikiLeaks has adjusted its strategies to take better advantage of a densely populated and globally networked media environment within the larger context of an ongoing political legitimation crisis. Chapter 6 extends this analysis to the case of Russiagate.